2008
DOI: 10.1111/j.1439-0531.2007.00956.x
|View full text |Cite
|
Sign up to set email alerts
|

Housing During Early Pregnancy Affects Fertility and Behaviour of Sows

Abstract: From 1.1.2013 EU legislation will permit stall-housing of dry sows for only 4 weeks post-service. Stalls are associated with compromised animal welfare, but group housing comes with risks from social confrontations. Studies on housing effects on fertility have produced contradictory results as systems are inconsistently defined. Effects of housing on pregnancy rate 28 days post-service (P28), early disruption of pregnancy (EDP) and behaviour were investigated in 12 replicates of 40 sows. Half of the animals we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 44 publications
0
34
0
2
Order By: Relevance
“…Comparison of group housing systems is difficult as there is large variation in terms of feeding strategies, group composition, size and stability, space allowance, floor material, and use of bedding (Kongsted, 2004;Munsterhjelm et al, 2008). For example, even the shape of the pen alters aggression in sows, with a rectangular pen reducing aggression compared to a square pen (Barnett et al, 1993b;Docking et al, 2000).…”
Section: Housing Types and Nutritionmentioning
confidence: 98%
See 1 more Smart Citation
“…Comparison of group housing systems is difficult as there is large variation in terms of feeding strategies, group composition, size and stability, space allowance, floor material, and use of bedding (Kongsted, 2004;Munsterhjelm et al, 2008). For example, even the shape of the pen alters aggression in sows, with a rectangular pen reducing aggression compared to a square pen (Barnett et al, 1993b;Docking et al, 2000).…”
Section: Housing Types and Nutritionmentioning
confidence: 98%
“…The housing of pigs in large groups is associated with more efficient use of building space and a reduction in labour (Turner et al, 2003b) but such an option may have consequences for sow welfare. If 'natural conditions' are mirrored, group size should be three to seven sows, similar to the size of wild groupings, and it has been suggested that groups larger than this may encounter difficulties when maintaining hierarchies (Munsterhjelm et al, 2008).…”
Section: Group Sizementioning
confidence: 99%
“…The litters were filmed and videos recorded from 1.00pm to 4.00pm on two consecutive days around 14 days of piglets´ age to observe sow behaviour regarding time budget. Behaviour was analysed using instantaneous sampling with sample intervals of 180 seconds (Martin and Bateson 1993 (Munsterhjelm et al 2008). If the sow was in the process of lying down at a sample point, the behaviour was recorded as the lying position assumed immediately after lying down, if at the sample point the sow was getting up, the subsequent behaviour was recorded.…”
Section: Reproduction and Behaviour Of Sowsmentioning
confidence: 99%
“…Regarding reproductive performance of the sow, an increased risk of repeat breeding has been associated with group housing after weaning in some studies earlier [17, 20]. However, in a large scale comparison, having all sows grouped after weaning did not appear to have a detrimental effect on reproductive performance [5].…”
Section: Grouping Sows After Weaning and Aimentioning
confidence: 99%